Socialization of Law Number 2 of 1981 and Law Number 8 of 1999 to Make it Happen Orderly Measuring Trade Through Tera and Retracting Measurement Tools and Education of Traders in Berastagi Market and Students of SMA Negeri 2 Kabanjahe - Ginting, Junedi; Gustanto (Talenta Publisher, 2024)
Sustainable Development Goals (SDGs) is a global action plan agreed upon by world leaders, including Indonesia, to end poverty, reduce poverty and protect the environment. SDGs contain 17 goals and 169 targets which are expected to be achieved by 2030. Universities are expected to help the government in strengthening SDGs programs. One of the 9th SDGs programs is